Cone-beam computed tomography compared to X-ray in diagnosis of extremities bone fractures: A study of 198 cases. (2019) - Ricci, Prof. M.; Boldini, M.; Bonfante, E.; Sambugaro, E.; Vecchini, E.; Schenal, G.; Magnan, B.; Montemezzi, S.
Abstract: CBCT is an imaging technique consisting of X-ray computed tomography, in which the x-rays are divergent, forming a cone. During 2015, a new model of CBCT, New Tom 5G XL (Verona), was used in the Radiology Department of The University of Verona, in collaboration with the Orthopaedics Department. Our study was carried out from October 2015 to October 2016 (198 patients). We compared CBCT with standard x-ray in the diagnosis of foot and anke fractures (and Lisfranc lesions), tibial plateau fractures, wrist and scaphoid fractures, elbow fractures. All patients were analyzed, of which 143 were positive or had documented bone lesions, while 55 were with no fractures seen. Of the 55 negative patients, 19 were considered positive at Standard RX, thus in 34.5% of cases the X-ray Standard examination overestimated the disease (false positive cases). Similarly, of the 143 positive patients, 21 were negative at RX, resulting in 14.6% of false negatives. We can say that if compared to standard X-ray, CBCT has higher sensitivity and specificity in the proper identification and typing of these kind of lesions, with low exposition dose if compared to MDCT. The most common rx-unrecognized fractures were in small bones of carpus and tarsus.